Stepwise PEG synthesis featuring deprotection and coupling in one pot - Mikesell, Logan; Eriyagama, Dhananjani N. A. M.; Yin, Yipeng; Lu, Bao-Yuan; Fang, Shiyue (Beilstein Journal of Organic Chemistry, 2021)
The stepwise synthesis of monodisperse polyethylene glycols (PEGs) and their derivatives usually involves using an acid-labile protecting group such as DMTr and coupling the two PEG moieties together under basic Williamson ether formation conditions. Using this approach, each elongation of PEG is achieved in three steps – deprotection, deprotonation and coupling – in two pots. Here, we report a more convenient approach for PEG synthesis featuring the use of a base-labile protecting group such as the phenethyl group. Using this approach, each elongation of PEG can be achieved in two steps – deprotection and coupling – in only one pot. The deprotonation step, and the isolation and purification of the intermediate product after deprotection using existing approaches are no longer needed when the one-pot approach is used. Because the stepwise PEG synthesis usually requires multiple PEG elongation cycles, the new PEG synthesis method is expected to significantly lower PEG synthesis cost.
Keywords: base-labile; monodisperse; PEG; polyethylene glycol; protecting group